(3eONd EOGQj heMGSHjs - (3HTjQ(B, (3GdYdGbs; (3eMehO TQa GdOjf(B, s ((3YeGf(B:s (3OGQ GdjGRhQj GdYdejI ddfTQ hGdJhRjY(B,s, 2008)
(3CgejI hCZQGV GdJNRjf, Gdeaghe GdYdej ddJNWjW HUhQI YGeI, GdJYQja HeLGd JNWjW GdeNRhf, eGPG fYfj HGdESJgdGc GdefJXe, GdJNWjW ddGSJgdGc GdeJZjQ eY HbGA GdGMJjGLGJ GdSfhjI KGHKI, CMJjGWj GdWhGQF Ch GdCeGf, eaghe GdSjWQI GdeNRfjI, CfhGY GdLQO, eQGLYI GdeNRhfs
(3HHdjhZQGajG(B: (3U(B.307s
Keywords: (3GOGQI GdehGOs; (3GdJNRjfs; (3GdJNWjWs